MAKNA SENI PERTUNJUKAN MUSIK TRADISIONAL GORDANG SAMBILAN DALAM UPACARA ADAT PESTA PERNIKAHAN PADA MASYARAKAT MANDAILING DI KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Suprianto "; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The gordang sambilan performance art is a performance art that was eroded by technological developments and the development of musical instruments. Performing arts on gordang contain elements of art and cultural heritage values that must be preserved and preserved. The gordang sambilan show for the Mandailing community is a show that must be present in every custom event. The purpose of the study was to determine the meaning of the symbolic situation, the meaning of education, and the meaning of religion found in gordang sambilan performing arts. This study uses qualitative methods with a symbolic interaction approach. The informants in this study amounted to 8 people, 4 people were mandailing traditional figures, 2 gordang sambilan players and 2 people who watched the gordang sambilan show using a purposive and accidental. Data collection techniques are carried out through observation, in-depth interviews and documentation. The results showed that the meaning of the symbolic situation in gordang sambilan performance in Mandailing Natal District was composed of physical objects including the main tools (gordang sambilan), musical instruments (gong, sarune, and mongmongan) and gordang sambilan costumes that were adopted from the Mandailing community. The meaning of education in gordang sambilan performing arts is social education, haromonisasi education, social strata education in people's lives, and teaches the meaning of togetherness and mutual love. The meaning of religion in the gordang show while giving an explanation in maintaining speech and prioritizing parents rather than self-interest. The gordang sambilan player focuses on the rhythm of the music and the positive attitude of the players who are cooperative in cooperation, compact, disciplined and consistent in maintaining and preserving the performances of gordang sambilan. Keywords: Meaning of the art music Gordang Sambilan, ceremony of marriage mandailing communities, mandailing natal district, north sumatera province